PENGARUH GREEN HUMAN RESOURCE MANAGEMENT, GREEN INNOVATION, PERCEIVED ORGANIZATIONAL SUPPORT DAN RISK TAKING TERHADAP CORPORATE SUSTAINABILITY - Anggi Putrie Utami; Netania Emilia (Universitas Bina Taruna Gorontalo, 2024)
This study aims to analyze the influence of Green Human Resource Management, Green Innovation, Perceived Organizational Support, and risk-taking on Corporate Sustainability. Sampling using purposive sampling technique with respondent criteria, namely the workforce from PT Cannet Elektrik Indonesia and PT Intermatra. The number of respondents used in this study was 125 respondents. The data analysis method uses the Structural Equation Model (SEM) and is processed using SPSS 23 software. The results of this study indicate that only Green Human Resource Management does not have a positive influence on Corporate Sustainability, while Green Innovation, Perceived Organizational Support, and Risk Taking have a positive influence on Corporate Sustainability.